ANALISIS EARLY WARNING SYSTEM BERDASARKAN TINGKAT PERMODALAN PERUSAHAAN ASURANSI - Winata, I Nyoman (P3M Trisakti School of Insurance (TSI), 2020)
This research has purposes: 1. to analyse the underwriting differences in ratio between a paid-up capital of less than Rp. 150 bn and a paid-up capital of inequality greater than Rp. 150 bn among insurance companies, 2. to analyse the impact of the underwriting differences in ratio between a paid-up capital of less than Rp. 150 bn and a paid-up capital of inequality greater than Rp. 150 bn among insurance companies.The hypotheses of this research are: 1. There are underwriting differences in ratio between a paid-up capital of less than Rp. 150 bn and a paid-up capital of inequality greater than Rp. 150 bn among companies that have gone public at BEI, 2. The undewriting differences in ratio between a paid-up capital of less than Rp. 150 bn and a paid-up capital of inequality greater than Rp. 150 M have a negative impact for insurance companies that have gone public at BEI, this means that the insurance companies that have a paid-up capital of inequality greater than Rp. 150 bn do not necessarily have a higher degree of underwriting differences in ratio. The method of data analysis used is a statistic test that is used to analyse the underwriting differences in ratio between a paid-up capital of less than Rp.150 bn and a paid-up capital of inequality greater than Rp. 150 bn among companies that have gone public at BEI. The results of the different test research (independent sample t-test) show that there are underwriting differences in ratio between a paid-up capital of less than Rp. 150 bn and a paid-up capital of inequality greater than Rp. 150 bn for companies that have gone public at BEI. The average underwriting ratio between a paid-up capital of less than Rp. 150 bn is much better compared to the average of underwriting ratio of a paid-up capital of an inequality greater than Rp. 150 bn. Thus the policy impact to determine a minimum paid-up capital for insurance companies has not been able to give improvement in the increase of underwriting ratio, this means the policy to determine a paid-up capital for insurance companies that have gone public have not given a positive result.